Update on Fatty Liver in Dairy Cattle with Major Emphasis on Epidemiological Patterns, Pathophysiology in Relationship to Abdominal Adiposity, and Early Diagnosis - Pedro Melendez; Pablo Pinedo (Dairy)
Fatty liver is a more common than expected metabolic disease affecting dairy cattle around parturition, which generates high economic losses for the dairy industry. The disease has evolved from a low incidence of moderate cases to a greater increase of severe cases in recent years. This evolution could be explained by the higher rate of genetic selection that has been carried out for milk production, which concomitantly brings pleiotropic genes that determine greater abdominal adiposity, ketosis, and other diseases. Abdominal fat is much more reactive, pro-inflammatory, saturated, and low in adiponectin than subcutaneous fat. In this review, we will mainly address the epidemiological aspects, the pathophysiology concerning the different types of fat depots (subcutaneous and abdominal), and the early diagnosis of the disease to carry out efficient control and preventive strategies.